The Efforts to Improve Teacherâs Competency in Learning Process Through The Academic Supervision in SMP Negeri 13 Dumai - Yulvisriani, Yulvisriani (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
In academic supervision, teachers need professional competence so that the quality of teaching isincreases. In this PTS study that examines the results of supervision of teachers at random from class VIIto class IX as many as 10 people consisting of 8 female and 2 male at SMP Negeri 13 Dumai AcademicYear 2016/2017. The measured parameters are the result of teaching preparation (syllabus and lessonplan) of teaching activities in the classroom. That is done during supervision for two cycles in onesemester. data of PTS analysis and academic supervision increase, teachers ability in general inpreparation of teaching cycle I reaches 28.30% and on cycle II reaches 28.83% mean that there is anincrease of 0.53%. while in learning activity in cycle I average 49.37% and cycle II 51.79% 2.42%increase. therefore it can be concluded the application of academic supervision can improve thecompetence of professionalism of teachers so that the quality of teaching increases.